The relationship between self efficacy and goal realization in Indonesia foodservice industry - Sarassina, Raden Roro Fosa (2016)
Low goal realization of local new franchise entrepreneurs in Indonesia is the main factor that motivates this study. The growth of Indonesia’s leading local foodservice chain new outlet is only at the average of 3.48% while the international counterparts is at 8.24% over the past 5 years. This study has two bifocal objectives namely to examine the direct effect of specified predictors on goal realization and to examine the indirect effect or mediating effects of specified predictors on goal realization. Quantitative method is the main research design used with the local franchisees as the unit of analysis. From the 230 questionnaire distributed, 100 completed questionnaires were returned, representing 44 percent response rate. The questionnaire consists of 70 items measuring nine constructs which are goal realization; plan enactment; implementation intention, implementation desire; goal intention; goal desire; self-efficacy; attitude; and subjective norms. Partial Least Square through SMART PLS is used as the analysis method. The empirical results show four direct impacts: the direct predictor of goal realization is plan enactment; the direct predictor of plan enactment is self-efficacy; the direct predictors of implementation intention are implementation desire and self-efficacy. The indirect relationships show that plan enactment mediates the relationship between self-efficacy and goal realization. The results indicate that the goal realization has shorter process compared to the underpinning theory. Based on the findings, this study recommends that for the local franchisees to be successful they need to have high plan enactment but must be assisted by self-efficacy. More often than not, most Indonesian franchisees only manage to reach the implementation intention with the level of self-efficacy and implementation desire that they may have.